Analisis Dampak Pajak Tangguhan, Ukuran Perusahaan, Dan Pertumbuhan Penjualan Terhadap Manajemen Laba Pada Perusahaan Retail - Natrion; Sri Waluya; Asrul Guc (Pasca Sarjana Universitas Satya Negara Indonesia, 2026)
ABSTRACT Financial statements can be defined as documents that present information regarding the financial condition of an entity, whether a company or organization, over a specific period. This study aims to determine the effect of deferred tax, company size, and sales growth on earnings management (an empirical study of retail companies listed on the IDX 2020–2024). The study population consisted of retail companies listed on the Indonesia Stock Exchange for the 2020-2024 period. A total of 40 companies were sampled. The sampling technique used purposive sampling. The data analysis method used multiple linear regression analysis with SPSS version 24 software. The type of data used in this study was secondary data obtained from annual reports and company sustainability reports. The results indicate that deferred tax burden has an effect on earnings management, company size has an effect on earnings management, while sales growth has no effect on earnings management